2009
DOI: 10.1038/nature08292
|View full text |Cite
|
Sign up to set email alerts
|

New particle formation in forests inhibited by isoprene emissions

Abstract: It has been suggested that volatile organic compounds (VOCs) are involved in organic aerosol formation, which in turn affects radiative forcing and climate. The most abundant VOCs emitted by terrestrial vegetation are isoprene and its derivatives, such as monoterpenes and sesquiterpenes. New particle formation in boreal regions is related to monoterpene emissions and causes an estimated negative radiative forcing of about -0.2 to -0.9 W m(-2). The annual variation in aerosol growth rates during particle nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
234
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 275 publications
(258 citation statements)
references
References 27 publications
18
234
3
3
Order By: Relevance
“…Mass spectral analysis showed that fractions of isoprene were incorporated in the SOA formed from the other BVOC. Suppression of nucleation by isoprene was similar to that described for isoprene/MT systems (Kiendler-Scharr et al, 2009b). However, compared to isoprene/MT systems the suppression of nucleation by isoprene was less effective for the VOC mixture emitted from stressed poplar.…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…Mass spectral analysis showed that fractions of isoprene were incorporated in the SOA formed from the other BVOC. Suppression of nucleation by isoprene was similar to that described for isoprene/MT systems (Kiendler-Scharr et al, 2009b). However, compared to isoprene/MT systems the suppression of nucleation by isoprene was less effective for the VOC mixture emitted from stressed poplar.…”
Section: Introductionsupporting
confidence: 76%
“…As has been shown by Kiendler-Scharr et al (2009b) the presence of isoprene in VOCs emitted from trees suppresses new particle formation. Kiendler-Scharr et al (2009b) presented a simple parameterization to describe the suppression as function of relative concentration of isoprene in the BVOC mixture.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations